PENGEMBANGAN MEDIA MOBILE LEARNING BERBASIS ANDROID MENGGUNAKAN ANDROID STUDIO PADA MATERI ENERGI LISTRIK IPA KELAS VIDI TINGKAT SD/MI - Erni Erni; Wulan Adetiya; Yuberti Yuberti (JIP Jurnal Ilmiah PGMI, 2021)
This research aim to develop Android-based mobile learning media using android studio on electrical energy material for 6th grade Elementary School. This research method is Research and Development (R&D) using 4D which consists of four stages, namely defining, planning, developing, and distributing stages. This research was conducted at SDN 2 Wates Timur and SDN 1 Tambahrejo by 10 students for the small-scale test and 30 students for the large-scale test in each school. The feasibility of android-based mobile learning media was tested using a product validation questionnaire by media experts, material experts and using a questionnaire response from educators and students. The results indicate that the percentage of media eligibility based on the validation of media experts and material experts is 82% in the very feasible category and 81% in the very feasible category. The responses of educators and students respectively obtained a percentage of 89% and 87.5% with a very feasible category. In conclusion, android-based mobile learning media using android studio on electrical energy material for 6th grade Elementary School is very feasible. Suggestions for further research to be able to develop appropriate similar media on other materials or subjects.